Quality Assessment of Oenological Tannins Utilising Global Selectivity Chemical Sensors Array (“Electronic Tongue”) - Puech, J.-L.; Prida, A.; Isz, S. (South African Journal of Enology and Viticulture, 2016)
Oenological tannin is a common name for food additives containing tannins utilised in winemaking practices. The main taste feature of oenological tannin is the taste sensation of astringency and bitterness. In the present paper, samples of various oenological tannins (oak, chestnut, gall, tara, querbacho, grape seed and grape skin tannins) were analysed by means of a tasting panel, measuring the flavour attributes bitterness, astringency, body, duration of flavour and similarity with wine tannins, and using the array of global selectivity chemical sensors (electronic tongue) “α-ASTREE” Liquid and Taste Analyzer (Alpha M.O.S., Toulouse, France). Principal component analysis of the electronic tongue outputs applied for different tannin solutions provides good discrimination according to their chemical nature. Consequently, three main classes of oenological tannins, namely gallotannins, ellagitannins and condensed tannins, could be identified and separated. The global output of the electronic tongue is quite responsive to changes in the bitterness and astringency of model quinine and alum solutions and, once calibrated (correlation coefficients of 0.976 (p<0.001) and 0.996 (p<0.001) respectively) could quantify their concentrations with good precision. The electronic tongue output was found to be correlated with the flavour attributes of oenological tannins. The best correlation was observed for bitterness. This fact could be explained by more constant calibration and lesser influence of any interfering factors on this attribute.